Standardized pre-bronchoscopy mechanical power and KPC resistance as predictors of mortality in ventilated ICU patients: a retrospective cohort study - Briones-Claudett, Killen H.; Briones-Zamora, Killen H.; Briones-Claudett, Mónica H.; Touriz Bonifaz, María A.; Briones-Zamora, Anahí D.; Briones Marquez, Diana C.; Grunauer, Michelle (Frontiers in Medicine, 2026)
BackgroundMechanical power (MP) quantifies the energy delivered by the ventilator per unit time and is linked to ventilator-induced lung injury and mortality in mechanically ventilated patients. Its prognostic value before high-risk interventions such as fiberoptic bronchoscopy remains uncertain. Standardization of pre-procedural ventilator settings may enhance the reliability of respiratory mechanics and MP assessment.MethodsWe conducted a retrospective, single-center cohort study of 30 ICU patients on invasive mechanical ventilation undergoing urgent bronchoscopy. A five-minute stabilization under volume-controlled ventilation with FiO₂ 1.0 and unchanged PEEP and respiratory rate was applied before scope insertion. Pre-procedure MP, gas exchange, and respiratory mechanics were recorded. The primary outcome was 28-day mortality. Logistic regression evaluated associations with clinical and microbiological predictors.ResultsMedian age was 66 years and 73% of patients were male. Median baseline MP was 13.6 J/min. Although MP ≥ 18 J/min was associated with impaired respiratory mechanics, it was not linked to mortality. In multivariable analysis, only Klebsiella pneumoniae carbapenemase (KPC) positivity independently predicted death (OR 14.6; 95% CI 1.8 − 116.5; p = 0.011), whereas MP was non-interpretable. Overall mortality was 26.7%.InterpretationIn critically ill ventilated patients undergoing urgent bronchoscopy, baseline MP under standardized ventilatory conditions did not independently predict outcome. Instead, KPC positivity emerged as the predominant determinant of mortality. These findings underscore the prognostic dominance of microbiological resistance over transient physiologic parameters and highlight the need to integrate rapid resistance profiling with ventilatory monitoring for risk stratification in ICU bronchoscopy critical need to integrate rapid resistance profiling, such as multiplex PCR for resistance gene detection, alongside standardized ventilatory monitoring for early risk stratification and targeted therapeutic intervention in ICU bronchoscopy.